Sentiment Analysis of Indonesian Movie Review using K-Nearest Neighbors and Information Gain - Ine Pristiyanti, Ria; Ali Fauzi, M.; Muflikhah, Lailil (International Journal of Engineering and Technology, 2018)
Movie review is a necessity for movie lover to get information about people opinion on the movie to watch. However, movie lover cannot read all of the movie review manually. It will be costly and time consuming. Therefore, automatic way to analyze them is needed. In this study, we use bag of word (BOW) model and utilize IG to select the best features before KNN is employed to classify the review into positive or negative. The result for using all of term for classification is better than the feature selection due to the elimination of term having low information gain value with 92% accuracy.Â